MONTHLY DYNAMICS OF ULTRASTRUCTURAL CHANGES IN THE RATS’ ADRENAL GLANDS AFTER SKIN BURNS CONCOMITANT WITH ADMINISTRATION OF 0.9% NaCL SOLUTION WITHIN THE FIRST SEVEN DAYS - Dzevulska, I.V. (World of Medicine and Biology, 2015)
Electron microscope examination on 1, 3, 7, 14, 21 and 30 day after 2-3 degrees burn injuries of the skin in area of 21-23% of the body in rats which were injected the first seven days of 0.9% NaCl solution at a dose of 10 ml per kg in the adrenal glands showed that severe termal injury causes reorganization of structural components of adrenal cortex of experimental animals. The nature and degree of electron microscopic changes depends on the term after burn injury. Compensative and adaptive changes in the structures of cortex combined with signs of destructive disorders that lead to the suppression of adrenal endocrine functions. The maximum level of destructive changes in the cells of the stroma and the parenchyma of the adrenal glands at the ultrastructural level seen after 7 days from the beginning of the experiment. In the late stage of toxemia and septiсotoxemia in rats, after which the skin were injected with 0.9% NaCl solution during seven days, even on 30 day of burn injury in the cortex and medulla of the adrenal glands was absent full compensation of destructive changes.